The Impact of Digital Transformation on the Job Performance: A Field Study on Jeddah Specialist Hospitals Employees - Alzahrani, Omar Khamis Saeed; Mujallid, Osama Abdulrahman (The Arab Journal of Administration, 2024)
The study aimed to identify the impact of digital transformation in its dimensions (technological infrastructure, legislation and policies, organizational culture, human resources) on the job performance of employees of specialized hospitals in Jeddah. The study relied on the descriptive analytical approach, and used the questionnaire as the main tool for collecting data from a random sample consisting of (290) members of the staff, including doctors, pharmacists, administrators, and technicians in specialized hospitals in Jeddah (Jeddah Eye Hospital - Al Aziziyah Hospital), and the data were analyzed using the SPSS program. The current study has concluded important results that may help support the trend towards digital transformation in all governmental and private health organizations across the Kingdom in general. It was found that the process of digital transformation and job performance in specialized hospitals in Jeddah Governorate was high. The study also concluded that the four hypotheses of the study and their various dimensions were rejected, and it concluded that there was a statistically significant effect at the level of (0.05) for digital transformation in its dimensions (technological infrastructure, legislation and policies, culture). Organizational, human resources) and job performance of employees of specialized hospitals in Jeddah. It also created statistically significant differences at the level (0.05) between the averages of the responses of the study sample members towards (employee performance) due to the age variable - and that the differences came between the two age groups (from 25 to less than 35 years) and (55 years and over) in favor of employees in the age group (from 25 to less than 35 years) with the highest arithmetic mean. It also found statistically significant differences at the level of (0.05) between the averages of the responses of the study sample members towards (digital transformation) Attributable to the academic qualification variable - and that the differences came between the two qualification categories (diploma) and (bachelor’s) in favor of employees with the academic qualification (bachelor) with the highest arithmetic average. The study recommended the need to be careful about implementing digital transformation in its various dimensions until the main goal of the application is achieved, which is improving the performance of employees. Which is reflected in improving the level of health service provided to beneficiaries.